EVALUASI SISTEM INFORMASI AKUNTANSI PENERIMAAN DAN PENGELUARAN KAS PADA PERUSAHAAN MANUFAKTUR - Nur Azizah; Nur Indah R; Kurnia Ekasari (Yayasan Education and Social Center, 2022)
In this study, one of the problems that was found was that PT. Hamifaro Jaya Lestari's cash receipts and disbursements accounting information system was not as good as it could be because it still used a manual system of recording by writing in a book and using Excel. Therefore, this could result in unrecorded transactions, preventing the organization from receiving daily precise and valid cash situations for decision-making purposThis study's objective is to build an Accounting Information Approach (AIS) for cash flow receipts and expenditures utilizing a modeling system based on Business Process Modeling and Notation (BPMN). The research technique is applied research, with a special emphasis on research and development (Research & Development / R&D). As a result of the research, the proposed BPMN. Based business process architecture will be evaluated by manufacturing companies. This research is valuable to the organization as an evaluation tool for the present Accounting Information System, which can be made more effective and efficient in numerous stages